Health Program Optimization in Islamic Boarding Schools from the Perspective of Maqashid Sharia - Isma Amelia; Muhammad Khoirul Malik; Luthfi Muhyiddin; Akhmad Anwar Dani (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the optimization of health insurance programs in Islamic boarding schools through the lens of Maqashid Sharia. Islamic boarding schools (pesantren), as religious-based educational institutions accommodating thousands of students, face various challenges in providing adequate and sustainable health services. The health insurance program initiated by the Health Social Security Administration Agency has emerged as a potential solution to improve health access within these institutions. Theoretical framework: The theoretical framework of this research is built upon the integration of Islamic legal philosophy (Maqashid Sharia) with public policy analysis in health management. Literature review: Previous literature highlights the significance of Maqashid Sharia in evaluating welfare-oriented programs, yet little attention has been paid to health program implementation in faith-based educational institutions. Methods: Using a qualitative method with a descriptive-analytical approach, this study collected data through in-depth interviews with pesantren administrators, students, and BPJS representatives, complemented by document analysis of regulations and policies related to health programs in pesantren. Results: The findings reveal that the health insurance program has brought significant benefits in ensuring access to health services and protecting student welfare, particularly in terms of hifz an-nafs. However, several obstacles remain, including limited awareness among stakeholders, insufficient socialization of the program, and administrative complexities in premium management. From the Maqashid Sharia perspective, the program contributes positively to the protection of life but requires further optimization to align with broader sharia objectives, such as safeguarding wealth and intellect. Implications: The implication of this study emphasizes the need for policy improvements, targeted socialization strategies, and integration of sharia-based health education in pesantren. Novelty: The novelty of this research lies in its interdisciplinary analysis, combining Islamic legal theory with contemporary health program evaluation, which offers a new perspective in the field of Islamic social welfare studies.